Differences in Help-Seeking Behavior among University Students during the COVID-19 Pandemic Depending on Mental Health Status: Results from a Cross-Sectional Survey - Lukas Guenthner; Sabrina Baldofski; Elisabeth Kohls; Jan Schuhr; Tanja Brock; Christine Rummel-Kluge (Behavioral Sciences, 2023)
Background: Current evidence suggests that a significant proportion of university students are affected by mental disorders and suicidal ideation. Despite this, a treatment gap exists. Therefore, the present study assessed students’ knowledge and past use of on- and off-campus mental health services and help-seeking intentions. Furthermore, resilience was investigated as a potential barrier to help-seeking behavior. Methods: Data were collected between April and May 2022 from N = 5510 students from Saxony, Germany. To compare dependent variables, subgroups were computed according to students’ mental health status. Variables were assessed using standardized questionnaires. Chi-square tests were used for comparisons between groups. Multiple regression models were used to investigate the influence of resilience on help-seeking behavior. Results: Between 34 and 38% (depending on the subgroup) of participants indicated that they were not aware of their universities’ psychosocial counseling services. Furthermore, between 17 and 19% of participants indicated that they were not willing to seek help from professional mental health services. Finally, the previously found negative effect of resilience on help-seeking behavior was confirmed. Conclusion: The results showed a lack of awareness regarding universities’ mental health services and a treatment gap among university students. Universities and healthcare providers need to educate students about mental health services and how to access them. Further research is needed to elucidate the differential impact of resilience on mental health and help-seeking.